2023
DOI: 10.1038/s41598-023-43800-9
|View full text |Cite
|
Sign up to set email alerts
|

Controlling crystallites orientation and facet exposure for enhanced electrochemical properties of polycrystalline MoO3 films

Konrad Trzciński,
Zuzanna Zarach,
Mariusz Szkoda
et al.

Abstract: This study focuses on the development and optimization of MoO3 films on commercially available FTO substrates using the pulsed laser deposition (PLD) technique. By carefully selecting deposition conditions and implementing post-treatment procedures, precise control over crystallite orientation relative to the substrate is achieved. Deposition at 450 °C in O2 atmosphere results in random crystallite arrangement, while introducing argon instead of oxygen to the PLD chamber during the initial stage of sputtering … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Moreover by selecting appropriate substrates and deposition parameters it is possible to tune the crystal orientation of epitaxial MoO 3 thin films. It has been demonstrated that when the (011) and (102) planes are exposed to the electrolyte, ion intercalation is favored, leading to improved electrochemical properties compared to cathode film with (00 k) face exposed (Trzciński et al, 2023). Hongliang et al (2021) deposited V 2 O 5 and V 2 O 5 -Au composite cathode.…”
Section: Transition Metal Oxidesmentioning
confidence: 99%
“…Moreover by selecting appropriate substrates and deposition parameters it is possible to tune the crystal orientation of epitaxial MoO 3 thin films. It has been demonstrated that when the (011) and (102) planes are exposed to the electrolyte, ion intercalation is favored, leading to improved electrochemical properties compared to cathode film with (00 k) face exposed (Trzciński et al, 2023). Hongliang et al (2021) deposited V 2 O 5 and V 2 O 5 -Au composite cathode.…”
Section: Transition Metal Oxidesmentioning
confidence: 99%
“…ASSLBs are increasingly being recognized for their enhanced safety features. To fully harness their capabilities, the integration of high-voltage cathodes is crucial [63][64][65][66]. This would elevate the energy density of solid batteries, positioning them as strong contenders against their liquid counterparts.…”
Section: Existing Research Gaps In Ssb Cathodesmentioning
confidence: 99%